Gloria London, Ancient Cookware from the Levant An Ethnoarchaeological Perspective - Tidmarsh, John (Journal of Hellenistic Pottery and Material Culture, 2017)
After decades of relative neglect so-called coarse wares have now emerged as a worthy focus of study in their own right and no longer merely as a relatively small (and often perfunctory) chapter in an excavation report. In particular, the study of cookwares has found its rightful place as a rich and endlessly rewarding field for archaeologists, ethno-archaeologists, ceramicists, historians and those in any way interested in the variety and evolution of cuisines across time and cultures. In fact, bearing in mind our fascination with the seemingly never-ending array of new cookery shows which emerge on prime-time television it is perhaps surprising that it has taken so long!